The Influence of the Use of Accounting Information Systems and Understanding of EMKM SAK on the Quality of Financial Reports - Fitrianti, Rosi; Murad, Ahmad (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study explores how the use of accounting information systems and understanding of EMKM SAK affect the quality of financial reports in MSMEs in East Lombok. Accounting information systems can help MSMEs optimize financial resources, while the application of EMKM SAK can help prepare credible, accountable, and objective financial reports. The method in this study uses a quantitative research method, the sample in this study were MSME actors in East Lombok Regency with a total of 70 respondents. The analysis in this study is Partial Least Square (PLS). The results of the study indicate that the use of accounting information systems has a positive and significant effect on the quality of financial reports in East Lombok. Understanding of micro, small and medium entity financial accounting standards (EMKM SAK) does not have a positive and insignificant effect on the quality of financial reports in East Lombok.